Diagnostic and management challenges of intraventricular neurocysticercosis presenting in the third trimester of pregnancy: A case report. (March 2021) - Ramesh, Devika; Maurya, Dilip K; Gopalakrishnan, Madhavan S; Pegu, Bhabani; Ananthakrishnan, Ramesh; Nair, Pradeep P; Keepanasseril, Anish
The diagnosis of neurocysticercosis in pregnancy is challenging, even in endemic areas, as other neurological conditions with similar manifestations are common. Obstetricians and physicians may be reluctant to do neuroimaging in pregnancy and often the availability is limited in endemic areas. Management of neurocysticercosis depends on the symptomatology. In those presenting with features of increased intracranial pressure early treatment is necessary, taking into consideration the gestational age and the maternal condition at presentation. Presence of intraventricular cysts causing obstructive hydrocephalus necessitates their removal due to the risk of intracranial hypertension which could be life-threatening, particularly peripartum. We report a case of a woman with intraventricular neurocysticercosis, who presented in the third trimester, and described the management dilemmas that were encountered. The differential diagnoses and other aspects of the medical and surgical management of neurocysticercosis in pregnancy are also discussed.